THE USE OF ACRONYMS IN NURSING ENGLISH: IMPLICATIONS FOR THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE - Fijo León, María Isabel (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper analyzes the use of acronyms in nursing English, and its implications for the development of the communicative competence of the speakers of this special language. The starting assumption is that profuse use of acronyms is a defining feature of scientific genre and hence of nursing language. Evidence for this assumption is provided by the data obtained from a corpus of articles published in specialized nursing journals. The paper is organized as follows. First, the term ‘acronym’ is defined. Then, nursing acronyms are classified according to their degree of lexicalization. Next, I focus on acronym formation. Finally, I deal with the rules that govern acronym usage, and examine several examples to see both compliance and non-compliance with these rules. From the analysis of these examples, several conclusions are drawn.